Outcome of patients with sarcoidosis refractory to TNF antagonists: a case series - Thery-Casari, Clémence; Jamilloux, Yvan; Bouvry, Diane; Chapelon-Abric, Catherine; Marquet, Alicia; Bielefeld, Philip; Schleinitz, Nicolas; Vukusic, Sandra; Girszyn, Nicolas; Fain, Olivier; Bonnet, Fabrice; Valeyre, Dominique; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: Tumor necrosis factor (TNF) antagonists have been reported as an efficient third-line therapy for sarcoidosis but there is no data regarding patients who do not respond to this treatment. Objective: To report the characteristics, the outcome and the response to therapy of patients with sarcoidosis resistant to TNF antagonists. Methods: Patients from the French STAT (Sarcoidosis Treatment with Anti-TNF) registry who were classified as non-responders and who were followed-up for >1 year were included. The response to further therapies was classified as complete response, or partial response, and the others were classified as non-responders. Results: Among the 132 patients from the registry, 14 were considered as non-responders to anti-TNF. Nine patients (66% of women; mean age 48 years) were analyzed. The mean number of organs involved was 4.2. Seven patients were previously treated with more than 2 immunosuppressive treatments. The mean duration of the anti-TNF treatment was 9 months (range, 3-24). After a mean follow-up duration of 58 months (median, 35; range, 19-128) a complete response was observed in 2/9 cases, a partial response in 5/9 cases, and 2/9 cases were considered as non-responders. In all but one patient, the immunosuppressant that allowed the clinical response had previously been used. Furthermore, the dosage was not necessarily increased to gain efficacy. Non-responders were treated by corticosteroids only because of their comorbidities or noncompliance. Conclusion: In patients who do not respond to TNF antagonists, previously used immunosuppressants may be useful. Excluding a differential diagnosis, assessing compliance and testing for anti-drug antibodies should be systematic.